Geographic loan diversification and bank risk: A cross-country analysis - Tu Dq Le; Van TH Nguyen; Tran Hung Son (Cogent Economics & Finance, 2020)
This study investigates the geographic loan expansion on bank risk using the aggregate data of 53 countries from 2005 to 2016 using the system generalized method of moments. Our findings show that global expansion tends to increase bank insolvency and reduce bank adjusted-risk-performance. Our findings further indicate loans distributed to advanced markets tend to reduce bank stability while the proportion of loans to other emerging markets and developing countries may have the potential to improve bank solvency and risk-adjusted-performance. As diversification is seen as a necessary strategy to diversify bank risks, bank managers should put more attention to emerging markets.
Keywords: F30; G20; 330; adjusted-risk-performance; bank stability; geographic loan diversification; global banking system